NUTRITION THROUGH LIFECYCLE - SARA ABRAHAM ([S.l.] : NEW AGE INTERNATIONAL PUB, 2016)
Have you ever thought about the following? Why do we eat? What should we eat? How is food related to physical and mental health? How does one maintain ideal body weight? Is Balanced Diet expensive? Is it possible to plan a Food Budget? How good is our Dietary Pattern? How do we plan diets for children? How can we take care of the nutritional needs during pregnancy and lactation? Can the working women plan nutritions and cost-effective packed lunches? What are the dietary tips for the elderly? Which foods are high in Cholesterol/Fat/Carbohydrate/Energy/Fibre? How true/false are our beliefs about food? Let the contents of this book enable you to find the answers.
eBooks on EBSCOhost
Keywords: Nutrition; Diet; Nutritional Physiological Phenomena; Nutrition; Alimentation; diet; Diet; Nutrition